The Influence of Income, Health Services and Social Services on Employee Welfare at Universitas Muhammadiyah Sumatera Utara in the Covid-19 Pandemic Situation - Nasution, Salman; Mujiatun, Siti; Khaira, Mutiah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The purpose of this study is to determine the effect on income, health services and social services of employees at the Universitas Muhammadiyah Sumatera Utara or abbreviated UMSU. In the COVID-19 pandemic situation, many socio-economic impacts occurred on companies in the world, including at the UMSU as a higher education institution. This study uses primary and secondary data with quantitative descriptive analysis methods. This study took 12 respondents as samples from employees at UMSU by taking samples at the UMSU Administration Bureau. The results of the study concluded that income had a positive but not significant effect on welfare. Health services have a positive effect on welfare, while social services have a positive and significant effect on income. This research proves that the leadership of UMSU, in this case the Chancellor of UMSU, is very interested in maintaining the economy and employee immunity during the Covid 19 period which is currently engulfing the world.